HEAVY METALS CONCENTRATIONS IN WATER, SEDIMENT AND BIOTA IN KELABAT BAY, BANGKA ISLAND - Zainal Arifin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
Kelabat Bay is a semi enclosed waters divided into two parts, i.e., outer part of Klabat bay facing the Natuna Sea (T Luar) and inner Kelabat bay surrounded by human activities and five river mouths (T Dalam). Study on metal concentrations on sediments and biota was carried out in March and July 2006. Water and sediment samples as well as biota were analyzed using Flame-Atomic Absorption Spectrophotmetry (Flame AAS). The result showed that concentrations of the dissolved heavy metals were generally low with ranged as follows, Pb(1,0 – 26,0 μg L-1), Cd(<0,1– 3,0 μg L-1 ), Cu(1–2,0 μg L-1) dan Zn(1,0–4,0 μg L-1). An average of metal concentrations in sediments were as follows, Pb (11,46 mg kg-1), Cd (0,10 mg kg-1), Cu (2,50 mg kg-1) and Zn(13,64 mg kg-1). Average concentrations of Pb, Cu dan Zn in T Dalam was about double compared to that of sediments of T Luar. However, no significant different was observed between west and south-east monsoon. In contrast, concentrations of Cd in sediment was similar throughout Kelabat bay and influenced by seasons. Accumulation of metals by fishes were mostly lower compared to that of shellfishes. The snail Strombus canarium accumulated the highest of Pb and Cu, cockle Anadara sp was for Cd and Zn.Keywords: heavy metals, water, sediment, biota, temporal variation, Kelabat Bay